3x+6+9=12

Simple and best practice solution for 3x+6+9=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6+9=12 equation:


Simplifying
3x + 6 + 9 = 12

Reorder the terms:
6 + 9 + 3x = 12

Combine like terms: 6 + 9 = 15
15 + 3x = 12

Solving
15 + 3x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + 3x = 12 + -15

Combine like terms: 15 + -15 = 0
0 + 3x = 12 + -15
3x = 12 + -15

Combine like terms: 12 + -15 = -3
3x = -3

Divide each side by '3'.
x = -1

Simplifying
x = -1

See similar equations:

| -3(4T-1)=-(t-14) | | 9h-27=36 | | 4/5x5/16 | | -5b+7-4b-2-b=-15 | | 4(3+4)-3=25 | | 2x+20=94 | | 5a+9b=360 | | 4/3T=-36 | | 4(3+4x)=25 | | 4c-8=5c+15 | | (x-7)(x+3)=24 | | 10p-7=24 | | -11.4-m=10.9 | | 20p-7=24 | | 37+(9x-1)=90 | | 3x/4-2/3=5/6 | | (3y+7)(-4x+2)= | | (6x^2+7)-(-4y^2+7)= | | 6x+15=64 | | sinx=73 | | (x+1)(10x)=(12x+2)x | | (6x+36)=(2x-5) | | 30=-3(-6-2z) | | -9x-22=-184 | | 6w^4+w^3-3w^2=0 | | 56+(7x-1)=90 | | (15/8)=((17-x)/x) | | 5n(4n+1)=0 | | 16+5a=31 | | 10x-6/3-5x | | 32-66= | | x-34=5x+2 |

Equations solver categories